PERKEMBANGAN TRANSAKSI CARDLESS UNTUK MEMPERMUDAH TRANSAKSI MASYARAKAT - Debby Ayu Aprilia (2022)
The form of the banking revolution brought a lot of convenience. These various conveniences have brought the economy to a higher stage so that efficiency is a major topic in the digital era and can help people to make daily transactions easier. With the existence of cardless transactions launched by banks in Indonesia to increase the efficiency of cash deposit and withdrawal transactions without using an ATM card at an ATM machine, now people can make transactions easier. Based on the study aimed at knowing the development of the implementation of the use of cardless transactions, both cash deposits and cash withdrawals at ATM machines, and knowing the developments in the use of cardless transactions, either depositing or withdrawing cash at ATMs, it can be concluded that cardless transactions are an important feature for the community. because it has an influence on the development of cardless to facilitate public transactions. This shows the public's interest in switching to using cardless. In this way, both the rest of society can take advantage of technological advances in the banking revolution for the advancement of the Indonesian economy.